HERMENEUTIKA GADAMER DALAM STUDI TEOLOGI POLITIK - Attamimi, Faisal (Hunafa: Jurnal Studia Islamika, 2012)
This article discusses Gadamers hermeneutics in the study of political theology. The question of meaning is at the heart of hermeneutic study. The significance or meaning comes from the German word "meinen" which means "in the mind or true". Thus, the meaning of a text, actions, relationships, and so on is what is in the mind of the author in implementing or generating text. According to Gadamers hermeneutics, the meaning is never involved any of the elements (agents and intentions), but the two elements that must be interpreted (acts, texts and the like) and its interpreter. The Gadamer outlook is what will be used in the view of political realities, particularly the relation between religion and state in the context of Indonesian-ness.Kata Kunci: Hermeneutik Gadamer, Politik, teologi, makna, teks, interpreter.